Toxicity of Eun-bi San Pharmacopuncture Injection in the Muscle of Rats - Jongcheol Lee; Hohyun Jeong; Eunhye Cha; Manyong Park; Sungyoul Choi; Taehan Yook; InJa Song; Sungchul Kim (Korean Pharmacopuncture Institute, 2015)
Objectives: This study was carried out to analyze the single-dose toxicity of Eun-Bi San pharmacopuncture injected into the muscle of Sprague-Dawley (SD) rats. Methods: All experiments were performed at Biotoxtech, an institution certified to conduct non-clinical studies under the Good Laboratory Practice (GLP) regulations. Six week old SD rats reared by ORIENTBIO were chosen for this pilot study. The reason SD rats were chosen is that they have been widely used in safety tests in the field of medicine, so the results can be easily compared with many other databases. The Eun-Bi San pharmacopuncture was made in a clean room at the Korean Pharmacopuncture Institute (KPI, K-GMP). The constituents of the Eun-Bi San pharmacopuncture are Angelicae gigantis radix, Strychni semen and Glycyrrhizae radix. These were extracted at low temperature and low pressure in an aseptic room at the KPI. Doses of Eun-Bi San pharmacopuncture, 0.25, 0.5 and 1.0 mL, were administered to the experimental groups, and a dose of normal saline solution, 1.0 mL, was administered to the control group. This study was performed under the apapproval of the Institutional Animal Ethics Committee of Biotoxtech Co., Ltd. Results: No deaths or abnormalities occurred in any of the four groups. No significant changes in weight, hematological parameters or clinical chemistry between the control group and the experimental groups were observed. To determine if abnormalities existed in any organs and tissues, we used microscopy to examine representative histological sections of each specified organ; the results showed no significant differences in any of the organs or tissues. Conclusion: The results of this study suggest that treatment with Eun-Bi San pharmacopuncture is relatively safe and that its clinical use may be beneficial. Further evaluations and studies on this subject will be needed to provide more concrete evidence in support of these conclusions.